Posted by brit on Monday, April 28, 2008 at 6:43pm.
Multiply both sides by b. (I am assuming that (b+1) and (b-1) are not denominators.)
3b-2+b = 4b-b(b+2/b-1)
3b-2+b = 4b-b^2-2+b
(b^2 = b squared.)
Combine like terms.
2b-2 = 5b-b^2-2
Add 2 to both sides.
2b = 5b-b^2
Bring all terms to the left side of the equation.
b^2-3b = 0
b(b-3) = 0
Therefore b = 3 or 0.
I hope this helps. Thanks for asking.
algebra2 - if a=5 and b=-3 4a-3b
Math(Please Check My Work.) - 3a^3b^2(-a^3b-a^2b^2)=-3a^9b^3-3a^6b^4 *is this ...
Equations - Can anyone check this equation out for me please... another way of ...
Math - [2a + 3b] [2a - 3b. May you please explain the steps if you can.
Algebra Problem - I've gotten confunsed. Please help. Solve: 2y-a = a + 3b ...
algerbra - my mom and I can not figure this one out please help!!!! -(a-3b+27) I...
math - what is the answer of this problem:-3(a+3b)+(-1)(a+3b)-7+3(3a+b)
algebra 1 - a+(3a-2a)-(4a-3b) Combine the "a" tems and you can reduce ...
algebra2 PLEASE - what are three important thing for an evaluating and ...
algebra - a^6b^8-a^4b^3+a^3b^5-a^3b^3 ???
For Further Reading